A qualitative study of patients' experience of recovery after a distal femoral fracture. Issue 10 (October 2019) - Phelps, Emma Elizabeth; Tutton, Elizabeth; Griffin, Xavier; Baird, Janis; ,
Highlights: After a distal femoral fracture, patients need support from others to manage at home and undertake their daily activities. Once discharged from hospital, patients may struggle with limited mobility. For some patients, their rehabilitation is hindered by a lack of confidence and support. Abstract: Purpose: This qualitative study was conducted as part of a feasibility study for TrAFFix, (ISRCTN92089567), a randomised controlled trial that will compare two surgical interventions used to fix distal femoral fractures. Our aim was to understand patients' experiences of treatment and the early phase of recovery after a distal femoral fracture. While, much is known about the experience of recovery from hip fracture, little is known about whether patients with other lower limb fragility fractures experience the same concerns and challenges. Materials and Methods: Semi-structured interviews were conducted with 11 patients participating in TrAFFix or their relative. Interviews were conducted face to face or by telephone. With agreement from participants, interviews were audio recorded and transcribed. Transcripts were analysed inductively using thematic analysis. As part of the user involvement for TrAFFix, we held a focus group with PPI representatives who had experience or knowledge of lower limb fractures, to learn about factors that might influence patients' recovery after a fragility facture. Data from the focus group relevant to themes from our thematic analysis are also presented. Results: Three themes were identified within patients' accounts of their experience. Our data revealed that: i) being informed about treatment and recovery was important to patients; ii) patients muddled through and found ways to manage at home, often needing the support of others; and iii) rehabilitation was arduous for patients who received limited rehabilitative support and at times lacked confidence to follow the instructions that they were given. Conclusions: Our findings highlight the struggle patients endure while recovering after a distal femoral fracture and the limited rehabilitative support they receive after discharge from hospital. They reinforce the need to ensure a patient feels informed about their treatment and recovery and the need for greater support for patients to manage at home and move with confidence.